(untitled) (Journal of Universal Science Research, 2025)
Recent studies indicate that patients with chronic heart failure experience a range of neurohumoral responses, including the activation of inflammatory cytokines such as tumor necrosis factor-alpha, interleukin-1, and interleukin-6. These inflammatory processes contribute to the development of anemia of chronic disease. The identification of hepcidin, a key regulator of iron homeostasis in chronic heart failure, has significantly advanced our understanding of the pathophysiological link between inflammation and anemia. Elucidating the interactions between inflammatory mediators and targeting the suppression of pathogenic pathways are essential steps in the development of more effective therapeutic strategies.